A2.14 CCR6 expression drives arthritis in a T cell dependent manner. (24th February 2016) - Bonelli, M; Puchner, T; Goeschl, L; Hayer, S; Niederreiter, B; Smolen, JS; Scheinecker, C; Blüml, S
Abstract : Backgrounds and objectives: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease, characterised by synovial infiltration of various inflammatory cells. Chemokines are involved in controlling the recruitment of different cell types into the synovial membrane. Increased production of MIP-3-a and accumulation of CCR6 expressing mononuclear cells can be found in joints of RA patients. CCR6 expression has also been reported on CD4 + T cells, in particular regulatory as well as Th17 cells. Recent data suggest that CD25 - Foxp3 + T cells upregulate CCR6 and promote arthritis. In this study, we investigated the role of CCR6 in the pathogenesis of arthritis using different arthritis models. Materials and methods: Clinical as well as histological signs of arthritis were investigated in the collagen-induced arthritis (CIA), K/BxN serum transfer arthritis and in the human tumour necrosis factor (hTNFtg) arthritis model, comparing wt and CCR6-/- mice. We analysed the phenotype of lymph node cells by flow cytometry and cytokine concentrations in serum. Anti-collagen antibodies and cytokines were measured by enzyme-linked immunosorbent assay. Results: Since CCR6 is an important component of the innate immune system we compared the development of arthritis in CCR6-/- mice in 2 different arthritis models known to be T cell independent, the K/BxN serum transfer arthritis and hTNFtg arthritis. In both models, we did not detect any significant differences in clinical signs of inflammation or histological severity of arthritis between wt and CCR6-/- mice. In additon, we could not detect differences in bone density between wt and CCR6-/- mice. To investigate the role of CCR6 as part of the adaptive immune system in the development of arthritis we induced CIA in wt and CCR6-/- mice. CCR6-/- mice were almost completely protected from CIA. Analyses of T cell subsets by flow cytometry revealed a significant reduction of CD25 - Foxp3 + T cells. Conclusions: These data suggest that CCR6 is not crucially involved in innate immunity driven arthritis, but is necessary for the development of autoimmune arthritis. Importantly, CCR6 is necessary for the generation of pathogenic CD25 - Foxp3 + T cells in CIA, suggesting an important function of CCR6 on T cells in the development of autoimmune arthritis.